Feasibility and utility of a panel testing for 114 cancer‐associated genes in a clinical setting: A hospital‐based study. Issue 4 (2nd April 2019) - Sunami, Kuniko; Ichikawa, Hitoshi; Kubo, Takashi; Kato, Mamoru; Fujiwara, Yutaka; Shimomura, Akihiko; Koyama, Takafumi; Kakishima, Hiroki; Kitami, Mayuko; Matsushita, Hiromichi; Furukawa, Eisaku; Narushima, Daichi; et al.
Abstract : Next‐generation sequencing (NGS) of tumor tissue (ie, clinical sequencing) can guide clinical management by providing information about actionable gene aberrations that have diagnostic and therapeutic significance. Here, we undertook a hospital‐based prospective study (TOP‐GEAR project, 2nd stage) to investigate the feasibility and utility of NGS‐based analysis of 114 cancer‐associated genes (the NCC Oncopanel test). We examined 230 cases (comprising more than 30 tumor types) of advanced solid tumors, all of which were matched with nontumor samples. Gene profiling data were obtained for 187 cases (81.3%), 111 (59.4%) of which harbored actionable gene aberrations according to the Clinical Practice Guidelines for Next Generation Sequencing in Cancer Diagnosis and Treatment (Edition 1.0) issued by 3 major Japanese cancer‐related societies. Twenty‐five (13.3%) cases have since received molecular‐targeted therapy according to their gene aberrations. These results indicate the utility of tumor‐profiling multiplex gene panel testing in a clinical setting in Japan. This study is registered with UMIN Clinical Trials Registry (UMIN 000011141). Abstract : The results of the TOP‐GEAR project (UMIN 000011141) indicate the utility of tumor‐profiling multiplex gene panel testing in a clinical setting in Japan.